Revealing the Transient Concentration of CO2 in a Mixed‐Matrix Membrane by IR Microimaging and Molecular Modeling. Issue 18 (25th March 2018) - Hwang, Seungtaik; Semino, Rocio; Seoane, Beatriz; Zahan, Marufa; Chmelik, Christian; Valiullin, Rustem; Bertmer, Marko; Haase, Jürgen; Kapteijn, Freek; Gascon, Jorge; Maurin, Guillaume; Kärger, Jörg
Abstract: Through IR microimaging the spatially and temporally resolved development of the CO2 concentration in a ZIF‐8@6FDA‐DAM mixed matrix membrane (MMM) was visualized during transient adsorption. By recording the evolution of the CO2 concentration, it is observed that the CO2 molecules propagate from the ZIF‐8 filler, which acts as a transport "highway", towards the surrounding polymer. A high‐CO2 ‐concentration layer is formed at the MOF/polymer interface, which becomes more pronounced at higher CO2 gas pressures. A microscopic explanation of the origins of this phenomenon is suggested by means of molecular modeling. By applying a computational methodology combining quantum and force‐field based calculations, the formation of microvoids at the MOF/polymer interface is predicted. Grand canonical Monte Carlo simulations further demonstrate that CO2 tends to preferentially reside in these microvoids, which is expected to facilitate CO2 accumulation at the interface. Abstract : CO2 highway : The CO2 concentration in a ZIF‐8@6FDA‐DAM mixed‐matrix membrane (MMM) during transient adsorption was visualized by means of the IR microimaging technique. CO2 molecules propagate from the ZIF‐8 filler, which acts as a transport "highway", towards the surrounding polymer. A high‐CO2 ‐concentration layer is formed at the filler/polymer interface. A microscopic explanation of the first stages of this phenomenon is suggested via molecular modeling.